A new class of C2 chiral photodimer ligands for catalytic enantioselective diethylzinc addition to arylaldehydes. Issue 36 (9th September 2015) - Ueda, Yuki; Yagishita, Fumitoshi; Ishikawa, Hiroki; Kaji, Yuki; Baba, Nozomi; Kasashima, Yoshio; Mino, Takashi; Sakamoto, Masami
Abstract: A new class of C 2 chiral materials was easily prepared by the photodimerization reaction of ( R )- N -phenethyl-2-chromonecarboxamide followed by recrystallization. Reduction of the photodimer gave the corresponding alcohol stereoselectively. Both C 2 chiral materials worked effectively as ligands for enantioselective ethylation of arylaldehydes using diethylzinc. Graphical abstract: